Polyaniline Nanoparticles: A Novel Additive for Augmenting Thermal Conductivity and Tribo-Properties of Mineral Oil and Commercial Engine Oil - Vinay Saini; Jayashree Bijwe (Lubricants, 2022)
The present work demonstrates the novel composition of nanoparticles (NPs) of polyaniline (PANI) solo and, in combination with particles of polytetrafluoroethylene (PTFE) ~230 nm, as a powerful additive (antiwear-AWA and extreme-pressure additive EPA) in lubricating oils. The concentration of PANI NPs varied from 1–4 wt.% in a base oil and commercial 5W30 engine oil. The tribo-performance was evaluated on a four-ball tester. The PANI-based oils significantly enhanced the load-bearing ability, and 3 wt.% of PANI NPs led to enhancement in EP properties by 220% in a base oil and 58% in engine oil. Additionally, hybrid combinations of NPs of PTFE with PANI in base oil were prepared by mixing in a ratio of 3:1 and 2:1 and were explored for possible tribo-synergism in EP properties. The hybrid nano-oils led to the highest reported ~ 535% enhancement in the load-carrying capacity of mineral oil. The lubrication mechanisms for enhanced tribo performance were linked with studies on a scanning electron microscope, an energy-dispersive X-ray analyzer, and with the use of Raman spectroscopy.